Community Renewable Energy in the Czech Republic: Value Proposition Perspective - Pechancová, Viera; Pavelková, Drahomíra; Saha, Petr (Frontiers in Energy Research, 2022)
The community renewable energy offers a lot of potential for sustainable projects differing in terms of regional governance, technology, social, and economic settings. However, the energy sector is often missing a systematic approach to community energy project data, and community projects are based on diversified value proposition designs. The paper introduces a new concept of value proposition canvas. Four regional case studies provide essential inputs for the novel community renewable energy value proposition canvas based on the triple bottom line concept. The argument of this study is that energy communities bring together multiple positive local impacts, moreover we offer novel, structured way of looking at its value propositions in form of triple bottom line value proposition canvas. The study results might serve for the new entrants to the low carbon energy communities and decision-making authorities in energy policy.